Pengaruh Kompetensi Pedagogik dan Manajemen Pembelajaran Terhadap Penjaminan Mutu Pada Universitas Sang Bumi Ruwa Jurai Lampung - Nurhadi Kusuma; Eri Purwanti (Universitas Mathla'ul Anwar Banten, 2017)
Quality assurance of education is a concept in education quality management. In the application of this concept any school or educational institution is directed to ensure that the educational services provided meet or exceed the expectations of its customers, both internal and external customers. Internal customers are teachers and school employees, while the primary external customers are learners. The results of this study indicate that pedagogic competence at the University of Bumi Bumi Ruwa Jurai Lampung significant influence on quality assurance that is equal to 59.80%. This is influenced by the purpose of teaching and in making a good, fast, and timely teaching program plan, a high quality assurance is a driver of quality assurance.